Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation

Biogenic green synthesis of monodispersed gum kondagogu (Cochlospermum gossypium) iron nanocomposite material and its application in germination and growth of mung bean (Vigna radiata) as a plant model - Raju, Dugyala; Mehta, Urmil J.; Beedu, Sashidhar Rao (IET Nanobiotechnology, 2016)
An eco-friendly green and one-pot synthesis of highly monodispersed iron (Fe) nanoparticles (NPs) by using a natural biopolymer, gum kondagogu (GK) as reducing and capping agent is proposed. The NPs synthesised were characterised by ultra-violet-visible spectroscopy, transmission electron microscopy, scanning electron microscopy and X-ray diffraction. As the concentration of gum and time increases, the intensity of NPs formation increased. The NPs were highly monodispersed with uniform circular shapes of 2-6 nm in size. The formed NPs were crystalline in nature which was confirmed by diffraction analysis. The conversion ratio of Fe ionic form to NPs was 21% which was quantified by inductively coupled plasma mass spectroscopy (ICP-MS). Fe is essential for plant growth and development. A study was conducted to examine the effect of these NPs on the growth of mung bean (Vigna radiata). The radical length and biomass was increased in seeds exposed to Fe NPs than the ions. The uptake of Fe NPs by the sprouts was also quantified by ICP-MS, in which Fe was more in mung bean seeds exposed to NPs. The -amylase activity was increased in the seeds exposed to NPs. The observed increase in the biomass by Fe NPs and seed germination may facilitate its application in the agriculture as an important cost-effective method for plant growth.
Keywords: alpha-amylase activity; Biogenic green synthesis; biological techniques; Biomass; Cochlospermum gossypium; diffraction analysis; enzymes; Fe; gum concentration; high-monodispersed iron nanoparticles; inductively coupled plasma mass spectroscopy; ionic-to-nanoparticle iron conversion ratio; iron; monodispersed gum kondagogu; monodispersed gum kondagogu iron nanocomposite material; mung bean germination; mung bean growth; Nanobiotechnology; Nanocomposites; nanoparticle formation; Nanoparticles; natural biopolymer; plant growth; plant model; scanning electron microscopy; size 2 nm to 6 nm; transmission electron microscopy; ultraviolet spectra; ultraviolet-visible spectroscopy; Vigna radiata; visible spectra; X-ray diffraction